PREVENTION OF COMPLICATIONS CAUSED BY MYOCARDIAL ISCHEMIA-REPERFUSION IN NONCARDIAC SURGICAL PROCEDURES - I. A. Kozlov (Бюллетень сибирской медицины)
In the next 20 years, the aging population will be a major factor affecting the characteristics of perioperative anesthesia tactics. Domestic researchers have reported that the incidence of cardiac complications after general surgical procedures in patients with middle and old age is 9.1%, and mortality in these complications reached 45.5%. Analyzed current data on myocardial ischemia-reperfusion, the etiopathogenesis of perioperative cardiac complications, recurrence of their development and the possible consequences. It is concluded that prevention and timely treatment of complications resulting from ischemia-reperfusion of the myocardium, with noncardiac surgical interventions is an important tactical (prevention of perioperative myocardial infarction, arrhythmias, cardiac death) and policy (prevention of cardiac remodeling and post-hospital disability of patients) anaesthesiological tasks. Research carried out in the Nrgovsky Research Institute of General Reanimatology showed that in the real practice Detsky index, Lee index and echocardiographic left ventricular ejection fraction did not provide high accuracy prediction of cardiac events. More informative proved preoperative determination of blood N-terminal part of the pro-brain natriuretic peptide (NT-proBNP). In assessing the predictive ability of NT-proBNP area under the ROC-curve achieved 0.86. NT-proBNP value 358 pg/ml and above provided 77% sensitivity and 85% specificity. The comparative assessment and recommendations on the use to reduce the risk of cardiac complications of β-blockers, statins, calcium channel blockers, nitrates, clonidine, dexmedetomidine, levosimendan and phosphocreatine. Phosphocreatine, introduced in practice domestic cardiac surgery and transplantology more than 20 years ago, continues to be studied and used at the moment. Recently demonstrated that perioperative phosphocreatine usage appointment in older oncological patients with a high risk of cardiac complications reduces the incidence of acute ischemia and delirium, shortens the length of stay the intensive care unit and hospital stay. It was concluded that the reduction in the incidence of cardiac events has undoubted relevance with noncardiac operations.